Mixed donor, phenanthroline photoactive MOFs with favourable CO 2 selectivity - Schmitt, Wolfgang (My University, 2020)
Mixed donor phenanthroline-carboxylate linkers were combined with MnII or ZnII to form photoactive MOFs with large pore apertures. The MOFs display high CO2 adsorption capacities, which consequently causes structural framework flexibility, and align with favorable metrics for selective CO2 capture. The photophysical properties of the MOFs were investigated, with the MnII MOF giving rise to short triplet LMCT lifetimes.